Early brain abnormalities in infants born very preterm predict under-reactive temperament. (May 2020) - Tamm, Leanne; Patel, Meera; Peugh, James; Kline-Fath, Beth M.; Parikh, Nehal A.
Abstract: Background: Early temperament may mediate the association between brain abnormalities following preterm birth and neurodevelopmental outcomes. Aims: This exploratory study investigated whether brain abnormalities in infants born very preterm predicted temperament. Study design: Infants born prematurely underwent structural MRI at term. Mother self-reported depression symptoms at the scanning visit, and the Infant Behavior Questionnaire-Revised-Short (IBQ-R-S) about their infant at 3-months corrected age. Subjects: Infants ( n  = 214) born at ≤32 weeks gestation (M = 29.29, SD = 2.60). Average post-menstrual age at the MRI scan was 42.72 weeks (SD = 1.30). The majority of the infants were male ( n  = 115), and Caucasian ( n  = 145) or African American ( n  = 58). The average birthweight in grams was 1289.75 (SD = 448.5). Outcome measures: Infant Behavior Questionnaire-Revised-Short (IBQ-R-S) subscales. Results: Multivariate regression showed white matter abnormalities predicted lower ratings on High Intensity Pleasure and Vocal Reactivity, grey matter abnormalities predicted lower ratings on High Intensity Pleasure and Cuddliness, and cerebellar abnormalities predicted lower ratings on Fear and Sadness IBQ-R-S subscales adjusting for gestational age and sex. The pattern of results was essentially unchanged when maternal depression and socioeconomic status were included in the model. Conclusions: Early MRI-diagnosed brain abnormalities in infants born very preterm were associated less vocalization and engagement during cuddling, decreased ability to take pleasure in stimulating activities, and lower emotionality in fear and sadness domains. Although replication is warranted, an under-reactive temperament in infants born preterm may have a neurobiological basis. Highlights: Brain abnormalities predicted under-reactive temperament in infants born preterm. White and grey matter abnormalities associated with less High Intensity Pleasure White matter abnormalities associated with less Vocal Reactivity Grey matter abnormalities associated with less Cuddliness Cerebellar abnormalities associated with lower Fear and Sadness ratings